2010
DOI: 10.3724/sp.j.1006.2010.00422
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Mapping of a Bacterial Blight Resistance Gene <I>Xa14</I> in Rice

Abstract: Bacterial blight of rice, which is a vascular bundle disease caused by Xanthomonas oryzae pv. oryzae (Xoo), is one of the most serious diseases of rice worldwide, and leads to the yield of rice reduced greatly. The dominant gene Xa14 is highly resistant to Philippine race 5 of bacterial blight. The gene was located at the distal end on the long arm of chromosome 4 by Taura et al. Near-isogenic line in the background of IR24, namely IRBB14 carrying the gene Xa14 has been developed at International Rice Research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Known genes and loci ( Xa ) conferring resistance to specific Xoo races (Table 1 ) were overlaid with the Manhattan plots (Additional file 3 : Figure S2 and Additional file 4 : Figure S3). Among the known Xa loci, the regions of Xa4, xa5, Xa7, xa13, Xa14 , Xa21, and xa25 (Wang et al 2001 ; Blair et al 2003 ; Chen et al 2008 ; Chu et al 2006a , b ; Bao et al 2010 ; Song et al 1995 ; Chen et al 2002 ) were identified as overlapping with significant SNPs in this study (Additional file 3 : Figure S2, Additional file 4 : Figure S3 and Additional file 5 : Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Known genes and loci ( Xa ) conferring resistance to specific Xoo races (Table 1 ) were overlaid with the Manhattan plots (Additional file 3 : Figure S2 and Additional file 4 : Figure S3). Among the known Xa loci, the regions of Xa4, xa5, Xa7, xa13, Xa14 , Xa21, and xa25 (Wang et al 2001 ; Blair et al 2003 ; Chen et al 2008 ; Chu et al 2006a , b ; Bao et al 2010 ; Song et al 1995 ; Chen et al 2002 ) were identified as overlapping with significant SNPs in this study (Additional file 3 : Figure S2, Additional file 4 : Figure S3 and Additional file 5 : Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Significant SNP loci exclusively associated with resistance to PXO112 in the indica panel (Additional file 5 : Table S2) clustered in the flanking region of Xa14 (Bao et al 2010 ) that ranges from 30,063,575 bp-32,807,203 bp in the long arm of chromosome 4 (Additional file 4 : Figure S3e). On the other hand, SNP loci located in the short arm of chromosome 5 namely, S5_440644 and S5_453169 were highly associated with resistance to all seven strains of Xoo (Additional file 3 : Figure S2, Additional file 4 : Figure S3 and Additional file 5 : Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have mapped Xa2 in IRBB2 ( He et al., 2006 ) , Xa14 in IRBB14 ( Bao et al., 2010 ) , Xa31(t) in Zhachanglong (ZCL) ( Wang et al., 2009 ), and Xo1 in CGS ( Triplett et al., 2016 ) within the regions corresponding to the Xa1 locus in IRBB1. We asked whether these loci, in which all four respective R genes have not yet been cloned, could confer disease responses similar or different from that of Xa1 , i.e., susceptible to PXO99 A and resistant to its mutant strain ΔTal3.…”
Section: Resultsmentioning
confidence: 99%
“…The cloning of a gene usually involves mapping of the gene and functional complementation of the lines otherwise lacking the gene or the functional allele. For Xa2 , Xa31(t) , and Xa14 , all three R genes were mapped in their respective donors within the regions, wherein Xa1 in IRBB1 was cloned ( He et al., 2006 ; Wang et al., 2009 ; Bao et al., 2010 ). The transgenic Kitaake plants containing putative Xa2 , Xa31(t) , and Xa14 genomic clones were resistant to Xoo strains lacking iTALEs and were susceptible to Xoo strains carrying iTALE genes.…”
Section: Discussionmentioning
confidence: 99%